Membranous Nephropathy Secondary to Graves’ Disease: A Case Report - Neves, Precil Diego Miranda de Menezes; Muniz, Monique Pereira Rêgo; Morgantetti, Giuliano Ferreira; Cutrim, Érico Murilo Monteiro; Macieira, Carlos de Andrade; Salgado-Filho, Natalino; Lages, Joyce Santos; Brito, Dyego José de Araújo; Cunha, Kaile de Araújo; Gatto, Giuseppe Cesare; Silva, Gyl Eanes Barros (Frontiers in Immunology, 2022)
Membranous Nephropathy (MN) is a form of kidney disease that is idiopathic in 70-80% of cases. Glomerular involvement in autoimmune thyroiditis can occur in 10-30% of patients, and MN manifests in association with Hashimoto Thyroiditis in up to 20% of the cases with glomerular involvement. Reports of MN associated with Graves’ Disease (GD) are extremely rare in current literature. Herein, we report the case of a 46-year-old admitted to the hospital with nephrotic syndrome and symptomatic hyperthyroidism due to GD. Kidney biopsy revealed a secondary MN pattern, with immunohistochemical staining for PLA2R was negative and thyroglobulin showed weak and segmental staining along the glomerular capillary, and anti-thyroid peroxidase (TPO) antibody was not performed. The patient was treated for GD with methimazole and prednisone and despite reaching clinical improvement after 8 months, proteinuria remained close to nephrotic levels. In this scenario, the patient was submitted to radioactive iodine and there was a dramatic reduction in proteinuria levels after treatment. In conclusion, GD association with MN is rare, and when present, diagnosis using PLA2R and immunohistochemistry can be useful in determining association. In addition, radioactive iodine therapy can be an effective treatment modality when preceded with immunosuppressive corticosteroid therapy.